Analisis dan Perancangan Sistem Electronic Marketing dengan Penerapan Tujuh Tahap Siklus Internet Marketing - Jemes Candra; Holong Marisi Simalango (Media Informatika, 2022)
PT. Wahana Decorindo or abbreviated as PT Wahadec is a company engaged in the Granite and Tiles industry. The purpose of this research is to make it easier for prospective buyers to find information related to Wahadec through the company's website. The research methods used in writing this research include data collection methods and methods of applying the seven stages of the internet marketing cycle. The data collection method was carried out in the survey, interview, and questionnaire stages, and the method of applying the seven stages of the internet marketing cycle from Rafi A. Muhammad. The result to be achieved is that the company's website can provide accurate information to prospective buyers through the company's website. The results obtained from this study are that the implementation of e-marketing at Wahadec has a positive impact because Wahadec has many advantages or positive factors in the Go/No-Go Opportunity Assessment Stage and builds E-marketing Applications at PT. Wahanadec is adjusted to the rules for making interface design (7Cs).